Latency and reactivation of JC virus in peripheral blood of human immunodeficiency virus type 1-infected patients. - Dubois, V (1997)
JC virus (JCV) acts as an opportunistic virus in immunocompromised human immunodeficiency virus type 1 (HIV-1)-infected patients. The role of peripheral blood cells in central nervous system invasion, before the onset of progressive multifocal leukoencephalopathy (PML), remains controversial. In order to clarify JCV latency or reactivation status in peripheral blood, 72 HIV-1-infected patients were studied, together with 7 HIV-1-positive PML patients and 50 blood donors. Blood leukocytes, plasma, and B lymphocytes were investigated by two complementary DNA amplification procedures within the early T and late VP1 JCV genes and two reverse transcription techniques for the detection of corresponding early transcripts and mRNAs. JCV DNA was detected in 40.3% of the HIV-1-infected patients but only 8% of the blood donors (P < 0.001). Leukocytes represented 82.7% of the positive samples, but plasma from 12 patients (41.4%) contained JCV DNA. B lymphocytes seemed to be involved in the natural history of JCV but did not represent the unique cell target. JCV DNA was intermittently found in blood, and JCV mRNAs for VP1 capsid protein were detected exclusively in one PML patient. Such observations demonstrate that JCV, when detected in blood, does not undergo active multiplication. They support the JCV hematogenous spread hypothesis, but do not indicate any direct link between peripheral virus and dissemination in the central nervous system at the time of immunodepression.